EVALUASI SISTEM PENGENDALIAN MANAJEMEN BERBASIS LEVERS OF CONTROL UNTUK MENUNJANG STRATEGI COST LEADERSHIP PADA CV. BMT SURABAYA - Amos Jovanka Wijaya; Sujoko Efferin (CALYPTRA, 2018)
In the era of globalization as now, requires every company to always make innovations and improvements in order to achieve targeted goals. Therefore, one way that can support it is by the implementation of a good business strategy in accordance with the company’s condition. Besides the implementation of a good business strategy is required also the implementation of Management Control Systems in accordance with the vision and mission of the company. BMT is a business entity which is engaged in fast ship expedition by applying several business strategies such as: maintaining the condition of the package, maintaining customers' trust, increasing employee motivation, and ultimately setting the price of lower cost (cost leadership). Thesis research is included in applied research where the researcher hopes to give evaluation and recommendation on CV. BMT’s management control system through the levers of control point of view. The research method used is interview, observation, and document analysis. Lack of supervision from supervisors and the lack of understanding of the vision, mission, and objectives of the company by some employees that cause the non-compliance of company regulations are some of the problems of implementing a management control system that hampers the company's business strategy. Improvements using a levers of control based management control system are chosen because they emphasize information systems that can maintain and change organizational behavior patterns. Recommendation based on levers of control point of view, expected to improve management control system that has been applied and can support the company's business strategy.